"PEOPLE'S DIPLOMACY" AS AN IMPORTANT BASIS FOR COOPERATION BETWEEN UZBEKISTAN AND KYRGYZSTAN - Adylbekova Bekzada Uzakbaevna (Web of Journals Publishing, 2025)
The article analyzes the diplomatic relations between Uzbekistan and Kyrgyzstan. It was established on February 16, 1993, after the collapse of the Soviet Union. After gaining independence, both republics began to build their bilateral relations on the basis of good neighborliness, mutual respect and cooperation. And this date is special for bringing a meaningful line to modern bilateral relations and defining new plans for long-term mutually beneficial cooperation. Since ancient times, the peoples of our countries have formed a commonality of interests, aspirations and destinies. All this has been preserved in our epics, written sources about the exploits of outstanding batyrs(heroes), emirs, legendary personalities who created their statehood. We have practically a common history, language, religion, culture, traditions and moral values, we had and still have a deep blood relationship. It was these relations that predetermined the need for further consistent development of friendship and mutually beneficial partnership between Kyrgyzstan and Uzbekistan.
Keywords: Uzbekistan, Kyrgyzstan, declaration on strategic partnership, strengthening friendship, good neighborliness, trust, people's diplomacy, people, border.